2020
DOI: 10.1186/s12871-020-01206-4
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of locoregional anesthesia in breast surgery? A systematic literature review focused on pain intensity, opioid consumption, adverse events, and patient satisfaction

Abstract: Background Breast surgery in the United States is common. Pain affects up to 50% of women undergoing breast surgery and can interfere with postoperative outcomes. General anesthesia is the conventional, most frequently used anaesthetic technique. Various locoregional anesthetic techniques are also used for breast surgeries. A systematic review of the use of locoregional anesthesia for postoperative pain in breast surgery is needed to clarify its role in pain management. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Conversely, some authors have reported similar results to our study, in which the use of PECS block did not significantly reduce perioperative opioid use when compared to MMA alone ( 29 , 47 , 48 ). A dual-centered, placebo-controlled RCT performed by Cros et al .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, some authors have reported similar results to our study, in which the use of PECS block did not significantly reduce perioperative opioid use when compared to MMA alone ( 29 , 47 , 48 ). A dual-centered, placebo-controlled RCT performed by Cros et al .…”
Section: Discussionsupporting
confidence: 89%
“…The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV. Several clinical studies and meta-analysis showing a significant impact of PECS blocks on opioid consumption have reported a marked reduction in PONV frequency when compared with control groups or with MMA regimens without peripheral nerve block ( 19 , 26 , 28 , 30 , 31 , 45 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…US-ESPB can be useful as a safe and effective method for regional analgesia. It may improve postoperative recovery, shortens hospitalization stay and determinate an opioidsparing effect (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic changes and cardiac arrhythmias are not uncommon in clinical practice, depending on including patient features, surgical treatment and drugs administered (1,2). Management in the day surgery clinic is challenging because of fluctuating blood pressures and heart rates, and an attentive approach is required to avoid complications during day plastic surgical treatment (3,4,5,6,7). Local infiltration anesthesia (LIA) with local anesthetic T. Bagatin et al Effect of local infiltration analgesia on hemodynamic function in different surgical procedures in day surgery solutions contains vasoconstrictors that are commonly used and may potentially affect the cardiovascular condition (8).…”
Section: Introductionmentioning
confidence: 99%